Successful Transfection of Lymphocytes by Ternary Lipoplexes. Issue 6 (December 1999) - Simões, S.; Slepushkin, V.; Gaspar, R.; de Lima, M. C. Pedroso; Düzgünes, N.
Abstract : Transgene expression in lymphoid cells may be useful for modulating immune responses in, and gene therapy of, cancer and AIDS. Although cationic liposome-DNA complexes (lipoplexes) present advantages over viral vectors, they have low transfection efficiency, unfavorable features for intravenous administration, and lack of target cell specificity. The use of a targeting ligand (transferrin), or an endosome-disrupting peptide, in ternary complexes with liposomes and a luciferase plasmid, significantly promoted transgene expression in several T- and B-lymphocytic cell lines. The highest levels of luciferase activity were obtained at a lipid/DNA (±) charge ratio of 1/1, where the ternary complexes were net negatively charged. The use of such negatively charged ternary complexes may alleviate some of the drawbacks of highly positively charged plain lipoplexes for gene delivery.